A tactical analgesic option for Durham and Cleveland police firearms medics: the journey. (2nd February 2019) - Carr, Gavin; Kyle, Tony; Wheatley, PC Sean; Mellor, Adrian
Abstract : Background: With an ever-increasing exposure to clinical situations, predominantly trauma, firearms medics at Durham and Cleveland police forces began to consider whether an increase in their scope of practice was needed; specifically, whether they could add analgesia administration to their clinical protocols. Considerations: The request was directed to the Tactical Medical Advisory Group (TMAG). This faculty comprises a clinical lead, emergency medicine doctors, military and civilian paramedics and tactical team medic (TTM) trainers. Analgesia in general was discussed, then potential analgesic agents were considered. The faculty agreed that the analgesic agent would have: to be available to all tactical team medics at all times, so should be highly portable); a minimal regulatory and training burden; a rapid effect with minimal side effects; and no conflict with prehospital medicine practice. Implementation: A 6-hour training course in methoxyflurane (Penthrox ® ) with summative assessments was designed and delivered by TMAG to all TTMs over a 4-week period. The chair of the TMAG agreed to be the signatory for the prescription-only medicine document and a standard operating procedure was drawn up. Sufficient stocks of methoxyflurane were then purchased and distributed across both police forces' armed response units, together with updated patient report forms, administration documents and feedback forms completed by TTMs after incidents.